INNOVATION TECHNOLOGY FOR THE USE OF CORN COBS FOR RENEWABLE ENERGY - Humena, Steven; Indriana; Pade, Satria Wati; Tooy, Dedie Tooy; Elly, Femi H; Leke, Jein R (International Interdisciplinary Conference on Sustainable Development Goals, 2024)
This research aims to examine the potential of corn cobs as a renewable energy source and explore optimal processing methods as well as the economic and environmental impacts of their use. Research methods cover various stages from data collection, laboratory experiments, technical and economic analysis, to environmental and social impact evaluation. Using quantitative and qualitative approaches to explore the potential for using corn cobs as a renewable energy source. Utilization of corn cobs as renewable energy is a potential solution in facing energy and environmental challenges. The research results show that corn cobs have significant calorific value and can be processed using methods such as briquette production. Although there are still challenges in terms of technology adoption and investment, the resulting economic and environmental potential is very promising. Community empowerment through corncob-based energy production can be a strategic step in developing renewable energy in rural areas. Briquettes as an Alternative Fuel. Production of briquettes from corn cobs offers a practical solution for people who need alternative fuel at an affordable price. The quality of briquettes produced from corn cobs is sufficient to meet energy needs in households and small industrial scales. In addition, briquettes from corn cobs are also cleaner to use compared to coal or firewood.